Donor and recipient risk factors for the development of primary graft dysfunction following lung transplantation - Jenkins, J. Asher; Verdiner, Ricardo; Omar, Ashraf; Farina, Juan Maria; Wilson, Renita; D’Cunha, Jonathan; Reck Dos Santos, Pedro Augusto (Frontiers in Immunology, 2024)
Primary Graft Dysfunction (PGD) is a major cause of both short-term and long-term morbidity and mortality following lung transplantation. Various donor, recipient, and technical risk factors have been previously identified as being associated with the development of PGD. Here, we present a comprehensive review of the current literature as it pertains to PGD following lung transplantation, as well as discussing current strategies to mitigate PGD and future directions. We will pay special attention to recent advances in lung transplantation such as ex-vivo lung perfusion, thoracoabdominal normothermic regional perfusion, and up-to-date literature published in the interim since the 2016 ISHLT consensus statement on PGD and the COVID-19 pandemic.